Moringa oleifera seed husks for methylene blue dye adsorption: kinetic, equilibrium, and thermodynamic analyses - Lopes, Carolina Almeida [UNESP]; Roledo, Cely [UNESP]; Dos Reis, Adriano Gonçalves [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2022)
Mole·ifera se·ed hu·sks (H-M·O) w· ere u·sed as adsorbent for the removal of methylene blue (MB) dye from an aqueous solution. The ads ·orbent was char·acterized by SE·M, ED·X, X·RD, F·TIR, B·ET, and p·HPZC. To evaluate adsorption capacity, the influences of p ·H, kinetics, isotherms, and thermodynamic prop·erties were anal·yzed. Characteri·zation tech·niques indic·ated that H-MO has het·erogeneous morp·hological charac·teristics with a spe·cific sur·face a·rea of 3.24 m2 g-1, mai·nly comp·osed of ce·llulose distr·ibuted in an amor·phous stru·cture. MB adsorption was favorable at pH values higher than pHPZC of 6.6, using an adsorbent dosage of 1.0 g L-1. Equilibrium was achieved in the first 240 min, and the pseudo-second-order model was suitable for describing the kinetic data. Freu ·ndlich was the mo·st adeq·uate model for descri·bing the isoth·erm cur·ves, pred·icting a max·imum adsor·ption capa·city of 122.7 mg g-1 at 24°C, hig·her tha·n oth·er natu·ral ad·sorbents. The ads·orption proc·ess w·as spo·ntaneous and exoth·ermic, indic·ating that lo·wer temper·atures fav·or the ad· sorption and th·at it is cont·rolled by p·hysical fo·rces. The da·ta presen·ted indic·ate the M·B has t·he pot·ential to be succ· essfully trea·ted by the eco-fr·iendly and l·ow-cost ads·orbent M. oleif·era seed h·usks.
Cascas da semente de Moringa oleifera para adsorção do corante azul de metileno: análise cinética, de equilíbrio e termodinâmica
Keywords: agricultural wastes; low-cost adsorbent; physisorption